The momentum of gender and the SDGs: a corpus-assisted study of Norwegian development aid discourse - Hilde Ousland Vandeskog; Jan Buts (Humanities & Social Sciences Communications)
Abstract This article analyses a corpus of documents produced by four Norwegian development aid NGOs. The aim is to assess whether the 2015 introduction of the Sustainable Development Goals (SDGs) resulted in salient discursive changes, specifically in usage patterns surrounding the concept of gender. The corpus data consists of 154 texts, with a total of ~900,000 tokens, gathered from funding applications produced between 2010 and 2020. We draw on methodological tools from corpus linguistics and critical discourse analysis to carry out an analysis in three stages. First, we take stock of the visibility of references to specific SDGs in the corpus by means of frequency counts. Second, we employ collocation tables to test the hypothesis that the adoption of the SDGs introduces temporal variation in usage patterns pertaining to gender that exceeds variation observed across different types of NGO documents. Third, we draw on collocation networks to examine specific shifts in the discursive function of the phrase gender equality. Overall, we find that while the textual imprint of the SDGs is clearly present in the texts produced after 2015, no extensive transformation regarding the articulations of gender can be noted. In our conclusion, we discuss our findings in the context of the relation between the SDGs and human rights discourse and discuss the implications of the observed relation between intertextuality, conceptual flexibility, and the translational process of norm diffusion.